Characterization of alkali treated Nelumbo nucifera fiber and properties of its reinforced composite. Issue 13 (1st December 2022) - Elango, Ananthakrishnan Harish; Kumar, Kalidas Vinoth; Loganathan, Thozhuvur Govindaraman; Priya, Rathnam Krishna; Shobana, Sutha; Balasubramanian, Manickam; Dharmaraja, Jeyaprakash
ABSTRACT: Natural fibers are being extensively used in recent technological and structural applications due to the need for biodegradable materials. This paper deals with extraction of new cellulosic fiber from the stem of Nelumbo nucifera ( Nn ) (lotus) and the investigations via physical, structural and thermal properties on the alkali-treated fiber were carried out. The XRD analysis of the Nn fiber provides the crystallinity index of about 52.53% that implies its high crystalline structure and own associated strength. The FTIR analysis proves the presence of alcoholic and alpha keto carboxylic acid in Nn fiber. Thermal stability of Nn composite is found around 210°C and the TGA results prove that the extracted as well as alkali-treated fibers provide a good reinforcement to the matrix, which can be well synthesized mechanically improved biocomposites. Test samples of three different weight % of Nn fiber with the epoxy basement are designated as L10, L15 and L20 to measure the tensile and flexural strength. Test sample with L20 as weight % exhibits better Young's and flexural modulus. Alkali treated Nn composite is an important candidate for the natural fiber reinforcement and such a category can serve as a good material for household applications.